Evaluation of lactobacillus probiotics as adjuvants for nasal immunization with chimeric pneumococcal vaccine - Leontieva, G. F. (2016)
Vaccine protection against photogenic gram-positive bacteria including different species of streptococci is an important problem of contemporary molecular biology. Streptococcal infections are most common bacterial infections surpassing by the economic losses all the infections excluding influenza. The gates of streptococcal infection, oral cavity or vagina, are covered with immune and non-immune mucosal cells that are the first line of defenses. Subcutaneous immunization not always stimulate the local immunity on mucosal surfaces. On the other hand, mucosal vaccination can provide an appropriate local immune response together with systemic protection. However, mucosal immunization often requires usage of special and effective adjuvants especially in case of vaccines based on recombinant proteins. For protection against Streptococcus pneumoniae infection, two chimeric recombinant proteins (PSPF and PSP) have been tested as vaccines. Recombinant proteins PSPF and PSP carry immunogenic epitopes from the respiratory pathogen including PspA, Spr1875 and PsaA. PSPF structure also carries a fraction of flagellin- FliC molecule in comparison with PSP, which does not have this fragment. This portion of PSPF was included as internal adjuvant intended for the stimulation of Toll-like receptor 5. In this work, the adjuvant capacity of two probiotic strains, Lactobacillus rhamnosus CRL1505 and L. rhamnosus L32 was evaluated. It was demonstrated that both lactic acid bacteria strains were able to provide adjuvant effects by enhancing the mucosal and systemic immune responses after their co-administration with the recombinant chimeric protein PSPF. The adjuvant effect of both Lactobacillus strains was significantly decreased after their thermal inactivation. However, the cell walls of bacteria showed a marked adjuvant activity. An improved protection against several S. pneumoniae serotypes after mucosal immunization of infant mice with PSPF vaccine with probiotic strains or their cell walls was also demonstrated here. The recombinant chimeric protein PSPF administered with immunomodulatory probiotic strains or their bacterial components would be a promising vaccine for immunization of humans against S. pneumoniae, particularly in children.